ХИЖИЙ КЛОП PERILLUS BIOCULATUS (HETEROPTERA, PENTATOMIDAE) ЯК АГЕНТ БІОЛОГІЧНОГО ЗАХИСТУ РОСЛИН - Barkar, V. P.; Markina, T. Yu. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2020)
This article presents an analysis of scientific literature on the ecological and biological features of the predatory bug Perillus bioculatus (Fabricius, 1775), a known entomophagous of Colorado potato beetle (Leptinotarsa decemlineata Say, 1824). The expediency of using this species as an agent of biological protection of plants, in particular potato plantations (Solanum tuberosum L, 1753) is considered. Domestic and European experience of stinkbug acclimatization in the 60-70s of the XX century is analyzed. In Ukraine, local populations of Perillus bioculatus are found in the Steppe and Forest-steppe zones, which indicates the ecological flexibility and adaptation of the species to local conditions, their favorable for the full development of insects. At this time, the biological features of P. bioculatus have been studied in sufficient detail, which is the basis for its economic use. The trophic specialization of the stinkbug is members of the family of Chrysomelidae, in particular the Colorado potato beetle. But in European countries there is a use of predators as food for other insect species. In parallel with the work on acclimatization in the second half of the last century in many countries began active research to determine the possibility of using Perillus bioculatus as an agent of biological plant protection. These studies are currently ongoing. Peculiarities of stinkbug breeding in artificial conditions, storage, methods of its introduction into agrocenoses are determined. Optimal modes of stinkbug retention have been developed. Air temperature + 25–27 0С, relative humidity 70-75%, photoperiod - 16 hours day / 8 hours night. According to the experience of domestic technical entomology, it is proposed to use the larvae of the mealworm beetle (Tenebrio molitor, Linnaeus, 1758) and the greater wax moth (Galleria mellonella Linnaeus, 1758) to feed the stinkbug under artificial conditions. The prospects of making artificial nutrient mixtures are noted. There is no need for sophisticated equipment to breed the stinkbug. It is quite suitable available, which is used to develop other entomophagous. For the needs of the biomethod, the most appropriate use of P. bioculatus in the preimaginal stage, as adult insects are able to leave the place of release, especially at high densities. It is shown that there is no effective technology of mass breeding and use of this species to this day.